Factors influencing the buisness performance of Amanah Ikhtiar Malaysia (AIM) business owners - Rahah, Ismail (2014)
For Malaysia to be a high income nation, it must be able to compete effectively with other developed nations in the region and global stage. Therefore, more employment and business opportunities particularly in micro and small scale business need to be created by the government. One of the government strategies to implement the entrepreneurship programs is through micro financing programs. However, despite the rise of micro business owners, the survival and business performance of these firms is also questionable. Therefore, the study was conducted to measure the business performance of AIM business owners in three years or since its establishment. In addition, this study was also conducted to determine the relationship between the source of financing and entrepreneurial culture with business performance of AIM business owners. A total of 420 questionnaires were distributed to the AIM business owners in Klang Valley region who are the recipients of microfinance program provided by AIM. However, only 386 questionnaires were returned and were usable for further analyses. All hypotheses were tested using SPSS version 22. Based on the correlation analysis‟ result, it was suggested that the source of financing and entrepreneurial culture is correlated to AIM business owners‟ business performance. Besides that, the linear regression results indicated a significant relationship between source of financing and entrepreneurial culture with the business performance even though the relationship showed was moderate. Based on the result, some recommendations were proposed together with the limitation of the study which provides opportunity for further research.